Penyuluhan Tentang Pendewasaan Usia Perkawinan di SMP N 1 Sungai Tebelian Tahun 2024 - Atri Rudtitasari; Dian Ika Pratiwi; Arum Seftiani Lestari; Ngaisah Tri Rahayu; Hearty Efifania Ose Payon (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Increasing the age of marriage is an effort to increase the age at first marriage, namely the minimum age of 21 years for women and 25 years for men. The aim is to find out the healthy age limit for marriage and the impact of early marriage and unwanted pregnancy. The activity method is counseling on preparation for menarche including surveys, determining implementation schedules and data collection, pre-tests, socializing activities with outreach media, namely videos and leaflets. The activity was held on June 12 2024 at SMPN 1 Sungai Tebelian which was attended by 59 students aged 12-15 years. Post test and evaluation of questionnaire data processing using the Paired Sample Test. The results of data analysis show changes in the increase in knowledge of young women in pre-test and post-test Sig values. (2-tailed) of 0.000 < 0.05. The conclusion is that there is a difference in the increase in knowledge before and after counseling on maturation during marriage at SMPN 1 Sungai Tebelian. This outreach activity increases students' knowledge about healthy marriage age limits and the impact of early marriage and unwanted pregnancies.